(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the актуal problems of implementing research results into educational practice, their underlying causes, and possible solutions based on modern pedagogical innovations. In particular, the issue of developing students’ media literacy competence is substantiated from a scientific and pedagogical perspective. The digital platform “CritiLearn” (Critical Learning), proposed by the author, is presented as a practical mechanism for integrating scientific developments into the real educational process. The content of the platform, its methodological structure, modules, interface, and sample lesson designs are comprehensively described.